2017
DOI: 10.1136/bmjopen-2016-015016
|View full text |Cite
|
Sign up to set email alerts
|

The eSMART study protocol: a randomised controlled trial to evaluate electronic symptom management using the advanced symptom management system (ASyMS) remote technology for patients with cancer

Abstract: IntroductionWhile some evidence exists that real-time remote symptom monitoring devices can decrease morbidity and prevent unplanned admissions in oncology patients, overall, these studies have significant methodological weaknesses. The electronic Symptom Management using the Advanced Symptom Management System (ASyMS) Remote Technology (eSMART) study is designed to specifically address these weaknesses with an appropriately powered, repeated-measures, parallel-group stratified randomised controlled trial of on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
83
0
9

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(93 citation statements)
references
References 56 publications
1
83
0
9
Order By: Relevance
“…Following development of the DCTAQ, our group carried on to create the e‐DCTAQ, the electronic equivalent of the DCTAQ for use with mobile phones and smartphones (to be reported on a separate publication). Briefly, symptom monitoring via the e‐DCTAQ was coupled with the development of risk algorithms and an alerting system that, whenever a symptom was reported as exceeding a pre‐determined cut‐point, generated and sent alerts to acute care clinicians for action (Maguire et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following development of the DCTAQ, our group carried on to create the e‐DCTAQ, the electronic equivalent of the DCTAQ for use with mobile phones and smartphones (to be reported on a separate publication). Briefly, symptom monitoring via the e‐DCTAQ was coupled with the development of risk algorithms and an alerting system that, whenever a symptom was reported as exceeding a pre‐determined cut‐point, generated and sent alerts to acute care clinicians for action (Maguire et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite this limitation, we believe that our rigorous investigation of the literature and involvement of cancer care experts in successive review rounds has led to a PRO measure, whose status seems to be in line with medical oncologists’ views and priorities for symptom reporting in clinical practice. Since initial development of the DCTAQ, we have embarked on additional work involving the DCTAQ (Maguire et al., ) and consultation with oncologists from around the world, who have confirmed the content format of the DCTAQ. Moreover, psychometric properties of the DCTAQ were investigated with patients with breast or colorectal cancer; hence, our findings might not apply to groups of patients with other types of cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to the prior study, the effects of the intervention by age groups were not provided. A larger study is currently ongoing to assess the effects of ASyMS on symptom burden, quality of life, supportive care needs, anxiety, self-care, self-efficacy, work limitations and cost effectiveness [50]. …”
Section: Symptom Reporting and Managementmentioning
confidence: 99%
“…Studies have also shown that mobile health apps can assist with medication management and provide reminders for doctor appointments with resulting improvement in self-care behavior, quality of life, and healthcare utilization [11]. In the cancer setting, mobile health apps have been designed for various uses which include providing education and support, monitoring symptoms and facilitating symptom reporting, monitoring medication adherence, promoting physical activity, and monitoring nutritional status and surgical care [12][13][14][15][16][17][18][19][20]. However, very few mobile apps have been tailored specifically for older adults with cancer who have complex healthcare needs, and/or for their caregivers who themselves frequently have health care issues [21].…”
Section: Scope Of the Problemmentioning
confidence: 99%